Economic Policy Uncertainty in the US: Does It Matter for Korea? - Seojin Lee (East Asian Economic Review (EAER), 2018)
Using the indicators of economic policy uncertainty developed by Baker et al. (2016), this paper investigates the effects of the US economic policy uncertainty on the Korea economic uncertainty as well as Korea-US foreign exchange risk. The key findings are that: (i) the degree of spillovers of policy uncertainty from the US to Korea is considerable but not comparatively high; (ii) the US policy uncertainty plays a stronger and more consistent role in Korean currency risk than Korea policy uncertainty and other macro variables. It implies that the economic policy uncertainty in the US is an important contributor to Korea-US exchange rates.
Keywords: C10; F20; F30; 330; Economic Policy Uncertainty; International Spillovers; Currency Risk; Implied Volatility; Korea Foreign Exchange Market